2022
DOI: 10.1038/s41598-022-21961-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on freeze–thaw damage characteristics of coal samples of different moisture contents in liquid nitrogen

Abstract: In this study, the surface crack-propagation law and pore damage characteristics of coal samples of different water contents after they undergo leaching in liquid nitrogen are investigated using a 4 K scientific-research camera, HC-U7 non-metal ultrasonic detector, nuclear magnetic resonance testing technology, and self-made multi-functional three axial fluid–solid coupling test system. Experimental investigations are conducted on coal samples of different water contents before and after they undergo liquid-ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The larger the initial water content, the greater the frost heaving force formed by water freezing and expansion and the more significant the fracturing effect. Wang et al [66] found that, in the process of LNFT, the coal water content was positively correlated with its surface frost heaving force and porosity, and the coal permeability showed stage characteristics. Li et al [67] found that, in the process of LNFT, the coal permeability increased exponentially with the increase in the water content.…”
Section: Effect Of Moisture On Lnfmentioning
confidence: 99%
“…The larger the initial water content, the greater the frost heaving force formed by water freezing and expansion and the more significant the fracturing effect. Wang et al [66] found that, in the process of LNFT, the coal water content was positively correlated with its surface frost heaving force and porosity, and the coal permeability showed stage characteristics. Li et al [67] found that, in the process of LNFT, the coal permeability increased exponentially with the increase in the water content.…”
Section: Effect Of Moisture On Lnfmentioning
confidence: 99%
“…The larger the initial water content, the greater the frost heave force formed by water freezing and expansion, and the more significant the fracturing effect. Wang et al [32] found that in the process of LNF, the water content of coal was positively correlated with its surface frost heaving force and porosity, and the permeability of coal showed stage characteristics; Li et al [33] found that in the process of LNF, the permeability of coal increases exponentially with the increase of water content. Dry coal samples mainly germinate new fractures on the basis of primary pores, while water-bearing coal samples germinate new fractures.…”
Section: Effect Of Moisture On Lnfmentioning
confidence: 99%
“…Wang X.Q. et al [21] carried out experiments based on a triaxial compression system to study the change rule of fractures in coal with different water contents, and the results showed that the original fractures of coal were developed after LN 2 cold dipping, and the expansion of surface fractures was positively correlated with the internal damage. Su S.J.…”
Section: Introductionmentioning
confidence: 99%